Body Composition and Cardiovascular Risk: A Study of Polish Military Flying Personnel - Agata Gaździńska; Stefan Gaździński; Paweł Jagielski; Paweł Kler (Metabolites, 2023)
(1) Background: Military personnel worldwide exhibit high rates of obesity. Obesity, and especially visceral obesity, contribute to various health issues, including type 2 diabetes and cardiovascular diseases (CVD). While BMI is commonly used to diagnose obesity, it has limitations and does not consider factors like fat distribution or muscle mass. This study aims to assess the relationship between BMI, percent body fat, waist circumference (WC), waist-to-height ratio (WHtR), and cardiovascular risk factors in Polish military flying personnel. Methods: This study involved 200 men from the Polish Air Force aged 38.8 ± 8.5 years. Anthropometric tests, body composition tests, and tests of biochemical markers of CVD were conducted. (2) Results: The prevalence of overweight and obesity varied based on the evaluation criterion; they were present in 63.5% of soldiers by BMI and in 52.5% by percent body fat; abdominal obesity was present in almost half (47%) of the surveyed soldiers according to WC and in 62.5% according to WHtR. All markers of obesity correlated positively with various biochemical markers of CVD, and 8.5% of subjects met the criteria for metabolic syndrome. (3) Conclusions: The prevalence of obesity in Polish military flying personnel, regardless of the evaluation criterion, is associated with significant metabolic complications in the form of lipid disorders and insulin resistance.